Infinitive Wh‐Relatives in Romance: Consequences for the Truncation‐versus‐Intervention Debate. (14th August 2019) - Villalba, Xavier
Abstract: Romance clitic left dislocation is widespread across all kinds of nonroot contexts, but it is forbidden in infinitive wh ‐relatives. This article investigates the extent and nature of this restriction and the consequences it raises for the truncation and intervention analyses of the left periphery of embedded sentences. We will show that current proposals cannot account for the whole gamut of data. In consequence, we will propose that infinitive wh ‐relatives display a maximally syncretic left periphery, whereas infinitive wh ‐interrogatives have a full‐fledged left periphery, crucially involving ForceP, because they are selected by a higher predicate. This crucial difference between infinitive relatives and interrogatives will also be shown to be consistent with the existence of specialized complementizers for the former but not the latter.